2018
DOI: 10.24093/awej/vol9no4.16
|View full text |Cite
|
Sign up to set email alerts
|

Silence of Thai Students as a Face-Saving Politeness Strategy in a Multicultural University Context

Abstract: Silence as a communicative act in face-to-face spontaneous interaction has been underinvestigated in linguistic politeness research in Thailand. With the recent increase in the influx of foreign students gaining admission into Thai universities yearly, the result is that such universities will be a coexistence of cultures. This study therefore aims to investigate the situational face-threat contexts where Thai students use silence as a politeness strategy. This aim is guided by the main research question of wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Socio-cultural norms practiced in Thailand clearly indicate that Thai people place importance in harmonizing society: they focus on caring for others and strive for better quality of life as seen in many other collectivist societies (Loh & Teo, 2017;Deveney, 2005). Therefore, rather than being direct and vocal about their opinions, they tend to prefer implicit communication as a way to be 'face conscious', not to attract attention, and to show their respect to others (Ambele & Boonsuk, 2018). Loh and Teo (2017) state that by graciously practicing this socio-cultural custom, Thai people make effort to 'preserve the status quo and tradition, hence stability as a virtue ' (p. 197).…”
Section: Socio-cultural Factors: Face-saving Strategy and Silencementioning
confidence: 99%
“…Socio-cultural norms practiced in Thailand clearly indicate that Thai people place importance in harmonizing society: they focus on caring for others and strive for better quality of life as seen in many other collectivist societies (Loh & Teo, 2017;Deveney, 2005). Therefore, rather than being direct and vocal about their opinions, they tend to prefer implicit communication as a way to be 'face conscious', not to attract attention, and to show their respect to others (Ambele & Boonsuk, 2018). Loh and Teo (2017) state that by graciously practicing this socio-cultural custom, Thai people make effort to 'preserve the status quo and tradition, hence stability as a virtue ' (p. 197).…”
Section: Socio-cultural Factors: Face-saving Strategy and Silencementioning
confidence: 99%
“…This leads to having respectful communications that consequently materializes in a meaningful teaching and learning process. Ambele and Boonsuk (2018) highlighted that the use of politeness strategy is influenced by one's culture. They indicated that poor language proficiency and uncertainty in word usage from an interlocutor can cause a change in hearer's mood.…”
Section: Literature Review Politeness Theorymentioning
confidence: 99%
“…Then, a teacher should teach by avoiding fanaticism in the class room. Not only in the class room, multicultural in university setting, has potential implication for sociocultural awareness (Ambele & Boonsuk, 2018) and avoiding fanaticism and its need in the community of learning. The multicultural education movement in Freire's opinion, that the flow of education has begun to open to the principles of understanding and acceptance, not just tolerance but rather leads to a form of respect for diversity, based on the need for educators teaching approaches shows a description of the support of the features of race, class, and gender in learning settings.…”
Section: Community Multicultural Integration Pattern In Environment-based Learningmentioning
confidence: 99%
“…Building good relations with parents/guardians of students can accelerate the achievement of school goals, both related to academic aspects and environmental aspects, and school culture. In many ways, the involvement of parents/guardians as the results of a study conducted by Kholis et al (2014) shows that the involvement of parents/guardians can accelerate the achievement of school goals, interacting with all element of schools (Ambele & Boonsuk, 2018). Schools have a variety of targets and objectives within a certain period of time.…”
Section: Table 1 Previous Multicultural Studies In the Worldmentioning
confidence: 99%
See 1 more Smart Citation